Cultural Predictors of Resilience in a Multinational Sample of Trauma Survivors - Raghavan, Sumithra S.; Sandanapitchai, Priyadharshiny (Frontiers in Psychology, 2019)
The present study aims to fill a gap in the study of resilience to trauma by examining resilience in a culturally diverse population. Approximately 70% of adults across the globe experience at least one traumatic event in their lifetime, yet resilience is a common response trajectory. This pilot study explored reactions to trauma and psychological resilience in an international sample of trauma-exposed participants. Participants were recruited online using the Amazon Mechanical Turk software and after completing an informed consent, were determined eligible to participate if they endorsed experiencing at least one traumatic event. Eligible participants then completed The Stressful Life Events Questionnaire, Brief Resiliency Scale, Ego Resiliency Scale, Posttraumatic Stress Disorder Checklist-Civilian Version, Brief Religious Coping Scale, and Multigroup Ethnic Identity Measure. The final sample included 200 trauma exposed adults from nineteen different countries worldwide, with a majority hailing from the United States, India, Sri Lanka and the Philippines. Results revealed that Asian participants scored significantly higher on resilience scales and endorsed higher levels of spiritually focused coping than other subgroups. Multivariate analyses revealed that these differences in resilience remained significant even after controlling for sense of ethnic identity and spiritual coping, suggesting that there may be culturally specific predictors of resilience within the Asian subgroup. Understanding variations in resilience will aid in developing culturally tailored interventions and pursuing a strengths-based approach to recovery from trauma. Limitations and implications are discussed.